Dietary crude protein reduction on growth and carcass performance of 22 to 42-day-old broilers reared under different temperatures - Oliveira, Will Pereira de; Oliveira, Rita Flávia Miranda de; Donzele, Juarez Lopes; Oliveira Neto, Adhemar Rodrigues de; Gomes, Paulo Cezar; Maia, Ana Paula de Assis; Campos, Paulo Henrique Reis Furtado; Gasparino, Eliane (Revista Brasileira de Zootecnia, 2013)
This study was conducted to verify the effects of dietary crude protein reduction on growth and carcass performance of 22-42-day-old broilers reared under different temperatures. Treatments were set up in a five by two factorial arrangement, with five crude protein levels (220, 210, 200, 190 and 184 g/kg) and two temperatures (21.6 and 32.2 ºC). Diets were isocaloric and essential amino acid-to-lysine ratio was maintained constant in all treatments. There was no interaction between crude protein reduction and environmental temperature for any of the parameters evaluated. Crude protein had no influence on feed intake. Nevertheless, weight gain and feed conversion ratio were linearly influenced by crude protein reduction. Worse performance was also observed in birds exposed to heat stress as compared with birds kept under thermoneutral temperature. There was no effect of crude protein reduction on breast and legs. Birds kept under heat stress had lower breast yield and higher leg yield as compared with broilers reared at 21.6 ºC. Any crude protein reduction in the range of 220 to 184 g/kg for 22 to 42-day-old broilers has a negative effect on their performance. Heat stress worsens broiler performance and breast yield.
Keywords: Breast yield; Heat stress; Temperature; Thermoneutral temperature